2016
DOI: 10.2136/sssaj2016.02.0052
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Soil Carbon in the Conterminous United States: Visible and Near Infrared Reflectance Spectroscopy Analysis of the Rapid Carbon Assessment Project

Abstract: Visible and near infrared reflectance spectroscopy (VisNIr) has been used across a number of spatial scales to predict soil organic carbon (OC) content. The rapid Carbon Assessment Project (raCA) is a nationwide project that collected 144,000+ soil samples from across the conterminous United States for C stock mapping using VisNIr. The objective of this study was to calibrate and validate the VisNIr soil OC and total C (TC) models with ~20,000 samples from raCA. Models were developed with either partial least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 32 publications
3
38
0
Order By: Relevance
“…Our simulated annealing analysis highlights SOC relationships (positive and negative) with climate variables (precipitation and land surface temperature), elevation (and terrain derivatives), and vegetation greenness (productivity and seasonality) that are consistent with previous literature describing SOC drivers across diverse environmental conditions (Evans et al, 2011;Hobley et al, 2015). In addition, when applying the simulated annealing framework to the independent datasets, a MODIS surface reflectance short wave infrared band (M06MOD4; Table S1) was one of the first five important variables predicting SOC, which is consistent with the infrared based methods used by the USDA for developing of the RaCA dataset (Wijewardane et al, 2016). The prediction capability of the infrared spectra (e.g., near infrared and midinfrared) for SOC can be attributed to the strong spectral absorption characteristics of soil organic matter and BD (the main components of SOC) in the infrared spectral bands .…”
Section: Global Biogeochemical Cyclessupporting
confidence: 85%
See 2 more Smart Citations
“…Our simulated annealing analysis highlights SOC relationships (positive and negative) with climate variables (precipitation and land surface temperature), elevation (and terrain derivatives), and vegetation greenness (productivity and seasonality) that are consistent with previous literature describing SOC drivers across diverse environmental conditions (Evans et al, 2011;Hobley et al, 2015). In addition, when applying the simulated annealing framework to the independent datasets, a MODIS surface reflectance short wave infrared band (M06MOD4; Table S1) was one of the first five important variables predicting SOC, which is consistent with the infrared based methods used by the USDA for developing of the RaCA dataset (Wijewardane et al, 2016). The prediction capability of the infrared spectra (e.g., near infrared and midinfrared) for SOC can be attributed to the strong spectral absorption characteristics of soil organic matter and BD (the main components of SOC) in the infrared spectral bands .…”
Section: Global Biogeochemical Cyclessupporting
confidence: 85%
“…We calculated model residuals against two fully independent datasets across both countries ( n =9239). Across CONUS we used 6,179 SOC estimates (2010) from the Rapid Carbon Assessment Project (RaCA, Soil Survey Staff and Loecke, ; Wijewardane et al, ) and 3,060 (2009–2011) SOC estimates from top soil samples extracted from the Mexican National Forest and Soils Inventory of the Mexican Forest Service (2009–2011; Figure S2). These independent datasets have been collected using different sampling designs and using different SOC calculation methods from our initial training dataset (INEGI and ISCN).…”
Section: Datasets and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study accomplished a similar decrease without using additional information. A performance of R 2 = 0.50 was reported in the Chinese vis–NIR SSL (Shi et al, ), whereas the results for the global SSL gave an R 2 of 0.57 (Ramirez‐Lopez et al, ); the best results in the literature were reported in the USA with R 2 = 0.94 (Wijewardane et al, ). A detailed review of results reported in the literature is given in Viscarra Rossel et al ().…”
Section: Discussionmentioning
confidence: 99%
“…While this methodology is an excellent way of increasing sampling density without greatly increasing analytical costs, the models may not be broadly applicable. Several research groups have been working to build large national and even international spectral libraries and associated databases with the intention of turning diffuse reflectance spectroscopy into a routine production tool (Baldock, Hawke, Sanderman, & Macdonald, 2014;Dangal, Sanderman, Wills, & Ramirez-Lopez, 2019;Nocita et al, 2014;Terhoeven-Urselmans, Vagen, Spaargaren, & Shepherd, 2010;Viscarra Rossel et al, 2016;Wijewardane, Ge, Wills, & Loecke, 2016, 2018.…”
Section: Introductionmentioning
confidence: 99%